Film for film capacitor, metal layer laminated film for film capacitor, and film capacitor
The film capacitor film, featuring a high-melting-point resin layer A and an oxygen-rich layer B, achieves high heat resistance and self-healing while enhancing productivity, overcoming the challenges faced by existing film capacitors for motor-driven vehicles.
Patent Information
- Application Number
- JP2021051277
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Existing film capacitors for motor-driven vehicles face challenges in achieving high heat resistance and self-healing properties while maintaining productivity, as current solutions like polyparaxylylene resin coatings are expensive, time-consuming, and have limited effectiveness in improving self-healing.
A film capacitor film with a resin layer A having a melting point of 180°C or higher and/or a glass transition temperature of 130°C or higher, and an outermost layer B with a thinner thickness and an oxygen atom content of 1.0% by mass or higher, which enhances heat resistance and self-healing properties while improving productivity.
The proposed solution provides a film capacitor with high heat resistance and self-healing properties, along with excellent productivity, effectively addressing the limitations of existing technologies.
Smart Images

Figure 0007666056000001 
Figure 0007666056000002 
Figure 0007666056000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a film for a film capacitor that serves as a dielectric of a film capacitor, a metal layer laminated film for a film capacitor, and a film capacitor. [Background technology]
[0002] In recent years, due to global environmental issues and other factors, the market has expanded for hybrid electric vehicles (HEVs) and plug-in hybrid electric vehicles (PHEVs), as well as electric motor-driven vehicles such as electric vehicles (EVs) and fuel cell vehicles (FCVs).As the market for these hybrid electric vehicles and electric motor-driven vehicles expands, the demand for the film capacitors used in these vehicles is also growing rapidly.
[0003] A film capacitor is a capacitor that uses a resin base film as a dielectric, and can achieve excellent frequency characteristics and temperature stability. Examples of base films for film capacitors include polyester resin films such as polypropylene (PP) resin film, polyethylene terephthalate (PET) resin film, and polyethylene naphthalate (PEN) resin film, thermoplastic resin films such as polyphenylene sulfide (PPS) resin film, and polyetherimide (PEI) resin film, which is an amorphous thermoplastic resin.
[0004] Among these films, polyetherimide resin films have been attracting attention as substrate films (Patent Document 1). This is because, when a film capacitor is used in a motor-driven vehicle or a motor-driven vehicle, heat resistance is required to withstand use in an environment of 120°C, and by using a substrate film made of a polyetherimide resin with a glass transition temperature (Tg) of 200°C or higher, excellent heat resistance and electrical properties such as voltage resistance and dielectric properties can be obtained.
[0005] On the other hand, base films with excellent heat resistance such as polyetherimide and polyphenylene sulfide generally have poor self-healing (SH) properties, and the capacitor capacitance decreases over long periods of use. In response to this, a technique is known for improving the self-healing properties by providing a coating layer on the base film (Patent Documents 2 and 3). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-300126 A [Patent Document 2] JP 2018-163950 A [Patent Document 3] International Publication No. 2007 / 080757 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the conventional technology, when achieving both heat resistance and self-healing properties, problems have been encountered in that a polyparaxylylene resin coating is used, which is expensive, takes a long time to form, has poor productivity, and has little effect in improving self-healing properties, or a silicone-based self-healing coating is used, which generates siloxane that may cause conductor failure in electric circuits when insulation breaks down. In view of the background of such conventional technology, the present invention aims to provide a film for a film capacitor that has high heat resistance and self-healing properties and is also excellent in productivity. [Means for solving the problem]
[0008] The above-mentioned problems can be solved by the following invention. That is, the film for a film capacitor of the present invention has a resin layer A having a melting point of 180° C. or more and / or a glass transition temperature of 130° C. or more, and a layer B having a thickness thinner than the resin layer A in at least one of the outermost layers of the film, and the oxygen atom content of the layer B is 1.0 mass % or more. Effect of the Invention
[0009] According to the present invention, it is possible to provide a film for a film capacitor which has high heat resistance and self-healing properties and is also excellent in productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The film for film capacitors of the present invention has a resin layer A having a melting point of 180° C. or more and / or a glass transition temperature of 130° C. or more, and in at least one of the outermost layers of the film, a layer B having a thickness thinner than the resin layer A, and the oxygen atom content of the layer B is 1.0 mass % or more. The film for film capacitors of the present invention will be specifically described below.
[0011] The film for film capacitors of the present invention has a resin layer A having a melting point of 180° C. or more and / or a glass transition temperature of 130° C. or more. The lower limit of the melting point of the resin layer A is preferably 205° C., more preferably 215° C., and although there is no particular upper limit, it is preferably 400° C., more preferably 350° C. The lower limit of the glass transition temperature of the resin layer A is preferably 180° C., more preferably 205° C., and although there is no particular upper limit, it is preferably 400° C., more preferably 350° C. By having the melting point and / or glass transition temperature of the resin layer A within the above range, insulation failure due to heat shrinkage or film breakage is unlikely to occur when the film for film capacitors is used in a high-temperature environment of 120° C. or more.
[0012] The thickness of the resin layer A of the present invention is not particularly limited, but is preferably 100 μm or less, more preferably 10 μm or less. By making the thickness of the resin layer A of the present invention 100 μm or less, it is easy to reduce the volume when made into a capacitor element. The lower limit of the thickness of the resin layer A is not particularly limited, but is preferably 0.50 μm, more preferably 1.3 μm, and even more preferably 1.6 μm. By making the thickness of the resin layer A 0.50 μm or more, it is easy to increase the dielectric breakdown voltage.
[0013] The raw material used for the resin layer A of the film for the film capacitor of the present invention is not particularly limited, but examples thereof include polyolefin resins such as polystyrene (PS) resin, polymethylpentene (PMP) resin, cyclic olefin (COP) resin, and cyclic olefin copolymer (COC) resin, polyester resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, and polyethylene naphthalate (PEN) resin, polyamide 6 (PA6) resin, polyamide 66 (PA66) resin, and polyamide 46 (PA46) resin. polyamide resins such as polyamide 4T (PA4T) resin, polyamide 6T (PA6T) resin, modified polyamide 6T (modified PA6T) resin, polyamide 9T (PA9T) resin, polyamide 10T (PA10T) resin, and polyamide 11T (PA11T) resin; polysulfone resins such as polysulfone (PSU) resin, polyethersulfone (PES) resin, and polyphenylsulfone (PPSU) resin; polyphenylene sulfide (PPS) resin, polyphenylene sulfide ketone resin, polyphenylene sulfide sulfone resin, and polyphenylene sulfide ketone polyarylene sulfide resins such as benzene sulfone resin, polyimide (PI) resins such as polyimide (PI) resin, polyetherimide (PEI) resin, and polyamideimide (PAI) resin, polyaryletherketone resins such as polyetherketone (PEK) resin, polyetheretherketone (PEEK) resin, polyetherketoneketone (PEKK) resin, polyetheretherketoneketone (PEEKK) resin, and polyetherketoneetherketoneketone (PEKEKK) resin, polytetrafluoroethylene (PTFE) resin (tetrafluoroethylene resin Polytetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) resin (also called tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin), tetrafluoroethylene-hexafluoropropylene copolymer (FEP) resin (also called tetrafluoroethylene-hexafluoropropylene copolymer resin), tetrafluoroethylene-ethylene copolymer (ETFE) resin (also called tetrafluoroethylene-ethylene copolymer resin), polychlorotrifluoroethylene (PCTFE) resin (also called trifluorochloroethylene resin),Examples of such resins include fluororesins such as polyvinylidene fluoride (PVDE) resin (also known as vinylidene fluoride resin), vinylidene fluoride-tetrafluoroethylene-hexafluoropyrene copolymer resin, polyacetal resin, liquid crystal polymer (LCP) resin, polycarbonate (PC) resin, polyarylate (PAR) resin, phenolic resin, polyurea resin, melamine resin, epoxy resin, and alkyd resin. Among these, it is preferable to use polysulfone resins such as polyetherimide resins, polycarbonate resins, polyphenylene sulfide resins, polyethersulfone resins, and polyphenylsulfone resins, polyimide resins, polymethylpentene resins, polyetheretherketone resins, polyetherketoneketone resins, and polyaryletherketone resins, which have excellent heat resistance at 150°C. Among resins with excellent heat resistance, it is more preferable to use polyphenylene sulfide resins, polyetherimide resins, polyphenylsulfone resins, and polyethersulfone resins, which have low dielectric tangents and are suitable for use as capacitors, and it is more preferable to contain at least one of these resins in an amount of 50% by mass to 100% by mass. These resins can also be modified, derivatives, and copolymers with other compounds. They may be used alone or in a mixture of two or more types.
[0014] The resin layer A of the film for film capacitors of the present invention may contain, within the range that does not impair its properties, antioxidants, light stabilizers, ultraviolet absorbers, plasticizers, lubricants, crosslinking agents, flame retardants, antistatic agents, heat resistance improvers, colorants, slip agents, antiblocking agents, inorganic particles, resin particles, inorganic compounds, organic compounds, etc. Each of these components may be used alone or in combination as necessary.
[0015] The film for film capacitors of the present invention has a layer B, which is thinner than the resin layer A, in at least one of the outermost layers of the film. The oxygen atom content of the layer B is 1.0 mass% or more. The oxygen atom content of the layer B is preferably 1.5 mass% or more, more preferably 21 mass% or more, and even more preferably 25 mass% or more. The upper limit of the oxygen atom content of the layer B is not particularly limited, but is preferably 50 mass%, more preferably 37 mass%, and even more preferably 34 mass%. By making the oxygen atom content contained in the layer B 1.0 mass% or more, the layer B becomes more likely to volatilize upon dielectric breakdown, and the self-healing property can be improved. By making the oxygen atom content contained in the layer B 50 mass% or less, a film with low blocking between films and excellent productivity can be obtained. The oxygen atom content of Layer B being 1.0 mass% or more means that the oxygen atoms in Layer B are 1.0 mass% or more when the total of hydrogen atoms, carbon atoms, sulfur atoms, silicon atoms, nitrogen atoms, and oxygen atoms in Layer B is taken as 100 mass%. The silicon atom Si content of Layer B described below can be interpreted in the same way.
[0016] The thickness of the layer B of the present invention is not particularly limited, but is preferably 10 nm or more, more preferably 50 nm or more. By making the thickness of the layer B 10 nm or more, it becomes easy to improve the self-healing property. In addition, the upper limit of the thickness of the layer B is not particularly limited, but is preferably 5.0 μm, more preferably 1.0 μm, even more preferably 0.50 μm, and particularly preferably 0.30 μm. By making the thickness of the layer B 5.0 μm or less, it becomes easy to increase the dielectric breakdown voltage.
[0017] Here, the thickness of each layer can be measured by observing the cross section in the width direction-thickness direction with a field emission scanning electron microscope and using its length measurement function, the detailed procedure of which will be described later. The atomic content of each layer can be obtained from the atomic fraction obtained by simultaneous Rutherford backscattering / hydrogen forward scattering spectrometry (Pelletron 3SDH manufactured by National Electrostatics Corporation), the detailed procedure of which will be described later (this is the same not only for the oxygen atomic content of layer B but also for the other atomic contents of each layer).
[0018] The content of silicon atoms Si in layer B is preferably 27% by mass or less. The upper limit of the content of silicon atoms Si in layer B is more preferably 15% by mass or less, more preferably 3.0% by mass or less, and even more preferably 1.0% by mass or less, and it is particularly preferable that layer B does not contain silicon atoms Si. By making the content of silicon atoms Si contained in layer B 27% by mass or less, it is possible to prevent deterioration of the capacitor characteristics due to siloxane generated at the time of dielectric breakdown.
[0019] It is preferable that layer B satisfies the following condition (i). Condition (i): The value XB calculated from the atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N, and oxygen atoms O contained in layer B based on the following formula (i) is 0.90 or less. Formula (a) XB = (atomic fraction of carbon atoms C in layer B + atomic fraction of nitrogen atoms N in layer B + atomic fraction of sulfur atoms S in layer B + atomic fraction of silicon atoms Si in layer B) / (atomic fraction of hydrogen atoms H in layer B + atomic fraction of oxygen atoms O in layer B) The upper limit of XB in the condition (i) is more preferably 0.80, even more preferably 0.70, and particularly preferably 0.65. XB is the ratio of atoms that tend not to evaporate during dielectric breakdown to atoms that tend to evaporate easily, and by making it 0.90 or less, it becomes easy to improve the self-healing property and the reliability of the capacitor. The lower limit of XB is not particularly limited, but is preferably 0.050, more preferably 0.20. By making XB 0.050 or more, it becomes easy to improve the adhesion between layer B and resin layer A.
[0020] The raw material used in layer B is not particularly limited, but for example, a resin or a low molecular weight organic compound can be used. From the viewpoint of adhesion with resin layer A, it is preferable to use a resin. The resin used in layer B is not particularly limited, but for example, polyolefin resins such as polystyrene (PS) resin, polymethylpentene (PMP) resin, cyclic olefin (COP) resin, and cyclic olefin copolymer (COC) resin, polyester resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, and polyethylene naphthalate (PEN) resin, polyamide 6 (PA6) resin, polyamide 66 (PA66) resin, and polyamide 46 (PA46) resin can be used. , polyamide resins such as polyamide 4T (PA4T) resin, polyamide 6T (PA6T) resin, modified polyamide 6T (modified PA6T) resin, polyamide 9T (PA9T) resin, polyamide 10T (PA10T) resin, and polyamide 11T (PA11T) resin; polysulfone resins such as polyethersulfone (PES) resin and polyphenylsulfone (PPSU) resin; polyphenylene sulfide (PPS) resin, polyphenylene sulfide ketone resin, polyphenylene sulfide sulfone resin, and polyphenylene sulfide polyaryl ether ketone resins such as aryl ether ether sulfone resins, polyimide (PI) resins such as polyimide (PI) resins, polyetherimide (PEI) resins, and polyamideimide (PAI) resins, polyaryl ether ketone resins such as polyether ketone (PEK) resins, polyether ether ketone (PEEK) resins, polyether ketone ketone (PEKK) resins, polyether ether ketone ketone (PEEKK) resins, and polyether ketone ether ketone ketone (PEKEKK) resins, polytetrafluoroethylene (PTFE) resins (also called tetrafluoroethylene resins), polytetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) resins (also called tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resins), tetrafluoroethylene-hexafluoropropylene copolymer (FEP) resins (also called tetrafluoroethylene-hexafluoropropylene copolymer resins), and tetrafluoroethylene-ethylene copolymer (ETFE) resins (also called tetrafluoroethylene-ethylene copolymer resins);Examples of the resin include fluororesins such as polychlorotrifluoroethylene (PCTFE) resin (also called trifluorochloroethylene resin), polyvinylidene fluoride (PVDE) resin (also called vinylidene fluoride resin), and vinylidene fluoride-tetrafluoroethylene-hexafluoropyrene copolymer resin, polyacetal resin, liquid crystal polymer (LCP) resin, polycarbonate (PC) resin, polyarylate (PAR) resin, phenol resin, polyurea resin, melamine resin, epoxy resin, alkyd resin, acrylic resin, polymethyl methacrylate resin (PMMA), polyurethane resin (PU), polyurethane acrylate resin, cellulose, cellulose derivatives (e.g., cellulose acetate, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, etc.), petroleum resin, terpene resin, and terpene phenol resin. Among these resins, preferred resins that have a low XB value and high self-healing properties are polyethylene (PE) resin, polypropylene (PP) resin, polystyrene (PS) resin, polymethylpentene (PNP) resin, cyclic olefin (COP) resin, and cyclic olefin copolymer (COC) resin, and other polyolefin resins, polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, and polyethylene naphthalate (PEN) resin, and other polyester resins, epoxy resins, alkyd resins, acrylic resins, polymethyl methacrylate resins (PMMA), polyacetal resins, liquid crystal polymer (LCP) resins, polycarbonate (PC) resins, polyarylate (PAR) resins, phenolic resins, cellulose, cellulose derivatives (e.g., cellulose acetate, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, etc.), petroleum resins, terpene resins, and terpene phenolic resins.
[0021] Among these raw materials, acrylic resins can increase heat resistance by crosslinking during formation, and epoxy resins and cellulose derivatives have high heat resistance due to the structure of the main skeleton, and by using them as raw materials for layer B, it becomes easy to extend the life at high temperatures when a capacitor element made of the capacitor film of the present invention is produced. In addition, since acrylic resins, epoxy resins, cellulose derivatives, and polyester resins are resins containing oxygen atoms, it becomes easy to increase the oxygen atom content of layer B and increase the self-healing property. From these points of view, it is more preferable that layer B contains at least one resin selected from acrylic resins, epoxy resins, cellulose derivatives, and polyester resins in an amount of 50% by mass to 100% by mass. These raw materials can also be modified bodies, derivatives, and copolymers with other compounds, or resins formed by applying in the form of a monomer and then polymerizing them. In addition, they may be used alone or in a mixture of two or more types.
[0022] In the film for film capacitor of the present invention, from the viewpoint of increasing the height of the protruding peaks on the surface on the layer B side and improving the slipperiness, it is preferable that the layer B contains two or more components that are incompatible with each other. Here, "components that are incompatible with each other" refers to two components that are not mixed uniformly at the molecular level, specifically, when the phases each mainly composed of two different components form a phase structure of 0.01 μm or more (whether or not the two components correspond to the "main component" here can be determined by whether or not the total content of the two components exceeds 50 mass% of the total components constituting the layer B). For example, when three or more components are contained in the layer B, if a phase mainly composed of one component forms a phase structure of 0.01 μm or more, it is considered to satisfy "containing two or more components that are incompatible with each other". When the components constituting the layer B are three or more, if two of the components satisfy the above requirements, it is considered to "contain two or more components that are incompatible with each other" regardless of whether the remaining components satisfy the above requirements.
[0023] Whether two or more components are incompatible or not can be determined by an electron microscope, a differential scanning calorimeter (DSC), or various other methods, as described in Polymer Alloys and Blends, Leszek A Utracki, hanser Publishers, Munich Viema New York, p. 64. The method of mixing two or more mutually incompatible components to increase the height of the protruding peaks is not particularly limited, but examples include a method of dispersing particles and resin in a solvent and leaving the particles as protrusions when dried, a method of mixing resins with high affinity and resins with low affinity with the material of resin layer A so that the amount of resin with low affinity is reduced, and the resin with low affinity is scattered on the surface of layer B as protrusions, a method of dissolving resins with high affinity for each solvent in two solvents with different boiling points, setting the temperature so that one solvent evaporates first when drying, so that the resin dissolved in the remaining solvent precipitates as protrusions later, and a combination of these methods.
[0024] As the combination of two mutually incompatible components used in layer B, a combination of an acrylic resin and a cellulose derivative, a combination of a cellulose derivative and an epoxy resin, and a combination of a methacrylic resin and an acrylic resin are preferred. These can be modified products, derivatives, and copolymers with other compounds, or resins formed by applying in the form of a monomer and then polymerizing. When applying a composition for forming layer B to resin layer A to form layer B, it is preferred to apply a coating liquid in which one of the raw materials is mixed in the form of a polymer and the other in the form of a monomer, and then polymerize the monomer to form layer B. In addition, if workability is important, a combination of an epoxy resin and silica, for example, is also preferred.
[0025] The film for film capacitors of the present invention preferably has a dielectric loss tangent of 2.0% or less from the viewpoint of extending the life of the film when used in a capacitor. From the above viewpoint, the upper limit of the dielectric loss tangent of the film for film capacitors is preferably 0.70%, more preferably 0.40%, and even more preferably 0.30%. By having the dielectric loss tangent of the film for film capacitors of 2.0% or less, the amount of heat generated during current application is reduced when the film is used in a film capacitor, and the life of the film capacitor is extended. The lower limit of the dielectric loss tangent of the film for film capacitors is not particularly limited, but is preferably 0.0010%, more preferably 0.010%. The dielectric loss tangent of the film for film capacitors can be reduced by using a resin with low polarity as the resin for the resin layer A, or by reducing the thickness of the layer B when a raw material with a dielectric loss tangent higher than that of the resin layer A is used as the raw material for the layer B. The dielectric loss tangent here refers to a value measured in accordance with JIS C2138-2007, and the detailed measurement method will be described later.
[0026] In the film for film capacitor of the present invention, when the dynamic friction coefficient is measured between the same surfaces of the two outermost layers, the surface with the larger dynamic friction coefficient is the a surface, the surface with the smaller dynamic friction coefficient is the b surface, and the dynamic friction coefficient between the a surfaces is μdaa and the dynamic friction coefficient between the a surface and the b surface is μdab, it is preferable that μdaa>μdab and μdab≦1.2 are satisfied. In addition, the dynamic friction coefficient between the b surfaces is μdbb. μdab more preferably satisfies μdab≦0.90, even more preferably μdab≦0.75, and particularly preferably μdab≦0.60. By satisfying μdaa>μdab and μdab≦1.2, the capacitor characteristics are not easily deteriorated and the slipperiness can be improved. Furthermore, by setting μdab to a low value, the processability can be further improved. The lower limit of μdab is not particularly limited, but is preferably 0.10. By setting μdab to 0.10 or more, it is easy to prevent the film for film capacitor of the present invention from slipping when wound into a wound body. The dynamic friction coefficient is measured in accordance with JIS K 7125 (1999) under a load of 200 g, at 25° C. and at 65% RH, and the detailed procedure is described later.
[0027] The method for making μdaa and μdab satisfy μdaa>μdab and μdab≦1.2 is not particularly limited, but includes a method of forming a resin layer A on a smooth substrate film or a mirror roll, and forming a layer B thereon by including two incompatible components in the raw materials. When μdab is high, μdab can be lowered by adjusting the mixing ratio so that the difference in the content of the two components is small. In addition, to make μdaa≦μdab, μdab can be lowered by the above-mentioned method, or the smoothness of the substrate film or roll used to form the resin layer A can be increased to increase μdaa, thereby making μdaa>μdab.
[0028] The value of μdbb is not particularly limited, but is preferably 0.10 or more, and more preferably 0.25 or more. By making μdbb 0.10 or more, it becomes easy to suppress the winding slippage when the film for film capacitor of the present invention is wound into a wound body. The upper limit of μdbb is not particularly limited, but is preferably 2.0, more preferably 1.5, and even more preferably 1.2. By making the value of μdbb 2.0 or less, it becomes easy to improve the processability.
[0029] The lower limit of μdaa is not particularly limited, but is preferably 0.10 or more, and more preferably 0.25 or more. By setting the lower limit of μdaa to 0.10 or more, it becomes easy to suppress the winding slippage when the film for film capacitor of the present invention is wound into a wound body. The upper limit of μdaa is not particularly limited, but is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.2 or less. By setting the upper limit of μdaa to 2.0 or less, it becomes easy to improve the processability.
[0030] In the film for film capacitor of the present invention, it is preferable that at least one of the outermost layer surfaces satisfies a load area ratio Smr1 ≧ 12% that separates the protruding peaks and the core. Since Smr1 focuses on the ratio of the protruding parts, the higher the value, the more effectively the contact area when it is brought into contact with another surface can be reduced. By making Smr1 12% or more, it becomes easy to improve the slipperiness of the film while keeping the dielectric breakdown voltage of the film high. Although there is no particular limit to the upper limit of Smr1, it is preferable that it is 49%, and more preferably 18%. By making Smr1 49% or less, it becomes easy to suppress deformation of the film surface when the film for film capacitor of the present invention is wound. In addition, Smr1 can be measured and calculated in accordance with ISO 25178-2: 2012 and ISO 25178-3: 2012, and a detailed measurement procedure will be described later.
[0031] The method for making the Smr1 of at least one outermost layer surface satisfy Smr1≧12% is not particularly limited, but an example is a method in which two incompatible components are included in the raw materials to form layer B. When Smr1 is low, Smr1 can be increased by adjusting the mixing ratio so that the difference in content between the two components described above is large, or by decreasing the solubility parameters (so-called SP values) of the two components.
[0032] It is preferable that the value XA calculated based on the atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N, and oxygen atoms O contained in the resin layer A satisfies XA>XB with respect to XB. Formula (b) XA=(atomic fraction of carbon atoms C in resin layer A+atomic fraction of nitrogen atoms N in resin layer A+atomic fraction of sulfur atoms S in resin layer A+atomic fraction of silicon atoms Si in resin layer A) / (atomic fraction of hydrogen atoms H in resin layer A+atomic fraction of oxygen atoms O in resin layer A) Since a higher XA tends to result in a resin with a higher degree of unsaturation and a more rigid structure, by ensuring that XA>XB, it becomes easier to improve self-healing properties while maintaining high heat resistance.
[0033] The ratio of the protruding peak height Spk-a on the a-side to the protruding peak height Spk-b on the b-side preferably satisfies Spk-b / Spk-a≧2.0, and the load area ratio Smr1-b separating the protruding peaks on the b-side from the core portion is preferably ≧12%. By making Smr1-b 12% or more, the slipperiness of the film can be improved. The upper limit of Smr1-b is not particularly limited, but is preferably 49%. By making Smr1-b 49% or less, it becomes easy to suppress the deformation of the film surface when the film for the film capacitor of the present invention is wound. By making Spk-b / Spk-a≧2.0 and Smr1-b≧12%, it becomes easy to obtain a film with excellent slipperiness. Spk-a and Spk-b can be measured and calculated in accordance with ISO 25178-2:2012 and ISO 25178-3:2012, and detailed measurement procedures will be described later.
[0034] The method for making Spk-a, Spk-b, and Smr1-b of at least one outermost layer surface satisfy Spk-b / Spk-a≧2.0 and Smr1-b≧12% or more is not particularly limited, but includes, for example, a method of forming layer B by including two incompatible components in the raw material. When Spk-b / Spk-a is low, Spk-b / Spk-a can be increased by increasing the difference in the content of the two components and increasing the solubility parameters (so-called SP values) of the two components. When Smr1-b is low, Smr1-b can be increased by adjusting the mixing ratio so that the difference in the content of the two components is large, or by decreasing the solubility parameters (so-called SP values) of the two components.
[0035] When the total thickness of the resin layer A and the layer B is T(F), it is preferable that the maximum valley depth Sv of both outermost layer surfaces of the film for film capacitor of the present invention satisfies Sv / T(F)<0.30. The upper limit of Sv / T(F) is preferably 0.20 for both sides. In other words, it is more preferable that Sv / T(F)≦0.20. Sv / T(F) means the size of the recess relative to the thickness of the film, and the higher it is, the more likely it is to cause insulation breakdown when compared at the same thickness. By making Sv / T(F) less than 0.30, it is easy to obtain a film with high voltage resistance characteristics. Sv can be measured and calculated in accordance with ISO 25178-2: 2012 and ISO 25178-3:2012, and a detailed measurement procedure will be described later.
[0036] The method for making Sv / T(F) less than 0.30 is not particularly limited, but an example of such a method is to form resin layer A on a smooth substrate film or mirror roll, and then apply a solution or liquid of the raw material of layer B thereon with a coater, and then dry to form layer B. If Sv / T(F) on the surface on the layer B side is 0.30 or more, Sv / T(F) can be lowered by adding a leveling agent to the raw material of layer B.
[0037] The maximum valley depth Sv of both outermost layer surfaces of the film for film capacitor of the present invention is preferably 0.10 nm or more on each side, and more preferably 10 nm or more. By making the maximum valley depth Sv of both outermost layer surfaces of the film for film capacitor of the present invention 0.10 nm or more on each side, it becomes easy to improve the processability. The upper limit of the maximum valley depth Sv of both outermost layer surfaces of the film for film capacitor of the present invention is preferably 5000 nm on each side. By making the maximum valley depth Sv of both outermost layer surfaces of the film for film capacitor of the present invention 5000 nm or less on each side, it becomes easy to obtain a film with high voltage resistance characteristics.
[0038] The metal layer laminated film for film capacitors of the present invention will be described below. From the viewpoint of integration, the film for film capacitors of the present invention is preferably a metal layer laminated film for film capacitors having a metal layer on the surface of at least one of the outermost layers, and more preferably a metal layer laminated film for film capacitors having a resin layer A, a layer B, and a metal layer in this order for the purpose of enhancing self-healing properties. Here, "having a resin layer A, a layer B, and a metal layer in this order" refers to a general embodiment in which the resin layer A, the layer B, and the metal layer are located in this order, regardless of whether there are other layers between the resin layer A and the layer B, or between the layer B and the metal layer.
[0039] Furthermore, in order to maintain high voltage resistance characteristics by increasing the smoothness of resin layer A made of a highly heat-resistant resin, the metal layer laminate film for film capacitors of the present invention has layer B on only one side of resin layer A, and has the metal layer on the layer B side, and when the surface with the larger kinetic friction coefficient measured between the two outermost layers is called side a and the surface with the smaller kinetic friction coefficient is called side b, it is particularly preferable that side b is on the layer B side as viewed from resin layer A.
[0040] The thickness of the metal layer is preferably in the range of 1 nm to 100 nm, more preferably 5 nm to 80 nm, and even more preferably 10 nm to 50 nm. The surface resistance of the metal layer is preferably in the range of 0.1 Ω / sq to 10 Ω / sq, more preferably 2 Ω / sq to 8 Ω / sq, and even more preferably 3 Ω / sq to 6 Ω / sq. This is because if the surface resistance of the metal layer is less than 0.1 Ω / sq, the self-healing property (also called self-repairing property) decreases, which is not preferable. On the other hand, if it exceeds 10 Ω / sq, the dielectric loss tangent may deteriorate.
[0041] The film for film capacitors of the present invention is preferably used as a dielectric film for capacitors, but is not limited to the type of capacitor. Specifically, from the viewpoint of electrode configuration, it may be either a foil-wrapped capacitor or a metal-vapor-deposited film capacitor, and is also preferably used in an oil-immersed type capacitor impregnated with insulating oil or a dry type capacitor that does not use insulating oil at all. In addition, from the viewpoint of shape, it may be a wound type or a laminated type. Among these, it is preferable to use it as a metal-vapor-deposited film capacitor including a metal layer laminated film, due to the characteristics of the film of the present invention. As a method for forming the metal layer, for example, a vacuum deposition method, a sputtering method, an ion plating method, a plating method, etc. are used. Among these methods, the vacuum deposition method, which has excellent productivity, is preferable. When the metal layer is vapor-deposited, an oil method, a tape method, etc. are used as a vapor deposition method. The vapor deposition pattern of the metal layer is not particularly limited, but preferable patterns include, for example, a T-margin pattern, a honeycomb pattern, a mosaic pattern, etc.
[0042] Next, the film capacitor of the present invention will be described. The film capacitor of the present invention is made using the metal layer laminate film for film capacitors of the present invention. The film capacitor of the present invention can be a part of an inverter and / or converter for an automobile (for example, an inverter for a hybrid electric vehicle, a converter for a hybrid electric vehicle, an inverter for an electric vehicle, a converter for an electric vehicle, etc.).
[0043] Next, an example of a method for producing the film for film capacitors of the present invention will be described. Note that the following example is a two-layer structure having a resin layer A and a layer B, but the film for film capacitors of the present invention may be a two-layer structure as long as it has a resin layer A and a layer B, or may be a three-layer structure having other layers. In the case of a three-layer structure or more, the layer with the largest thickness and a melting point of 180°C or more and / or a glass transition temperature of 130°C or more is the resin layer A.
[0044] First, the method of forming the resin layer A includes a method of supplying the raw material of the resin layer A to an extruder, melt-extruding it from a slit-shaped nozzle such as a T-die, and solidifying it on a cooling drum or the like to form the resin layer A, a method of applying the raw material of the resin layer A in a solution or liquid form to a substrate film such as a polyolefin film, a polyethylene terephthalate film, a polyimide film, or a film obtained by silicone-coating them to enhance releasability with a coater, and then drying it to form the resin layer A, and a method of casting the liquid on a casting belt and then drying it to form the resin layer A. Among these, from the viewpoint of improving the smoothness of the resin layer A, it is preferable to perform either of the following methods: a method of applying the raw material of the resin layer A in a solution or liquid form to a substrate film with a coater, and then drying it to form the resin layer A, or a method of supplying the raw material to an extruder, melt-extruding it from a slit-shaped nozzle such as a T-die, and solidifying it on a cooling drum or the like to form a film, and then stretching it uniaxially or biaxially to form the resin layer A. When resin layer A is formed on a base film, resin layer A may or may not be peeled off from the base film before forming layer B. From the viewpoint of improving transportability, however, it is preferable to form layer B without peeling.
[0045] Examples of a method for forming layer B on one surface of resin layer A include a method in which a solution or liquid raw material for layer B is applied onto resin layer A with a coater and then dried, and a method in which the raw material for layer B is vacuum-deposited onto resin layer A. From the viewpoint of increasing the protrusion height of the formed layer B, it is preferable to form it by a method in which a solution or liquid raw material for layer B is applied onto resin layer A with a coater and then dried.
[0046] When forming the layer B by coating one surface of the resin layer A, the coated surface of the resin layer A may be subjected to a surface treatment such as corona discharge treatment in advance. By performing a surface treatment such as corona discharge treatment, the wettability of the coating composition to the coated surface is improved, the coating composition is prevented from being repelled, and a uniform coating thickness can be easily achieved. When laminating a metal layer on the obtained film consisting of the resin layer A and the layer B, the method is not particularly limited, but it is preferable to vapor-deposit the metal on the layer B by vacuum deposition. The metal used for vapor deposition is preferably aluminum. At this time, other metal components such as nickel, copper, gold, silver, chromium and zinc can also be vapor-deposited simultaneously with or successively to the aluminum. When laminating a metal layer on a film consisting of the resin layer A and the layer B by vapor deposition, the vapor-deposited surface of the film may be subjected to a surface treatment such as corona discharge treatment before vapor deposition. By performing a surface treatment such as corona discharge treatment, the adhesion of the vapor-deposited metal to the film can be increased.
[0047] When forming layer B, it is preferable to crosslink the components of layer B. The crosslinking method is not particularly limited, but includes a method in which a compound having multiple reactive sites is used as the raw material of layer B and crosslinked by heat or ultraviolet light. Examples of compounds having multiple reactive sites include acrylates having two or more vinyl groups, epoxies having two or more epoxy groups, and condensates of melamine and formaldehyde. Among these, it is preferable to use acrylates having two or more vinyl groups from the viewpoint of increasing the oxygen concentration of layer B and enhancing the self-healing property. In order to promote the crosslinking reaction, when forming layer B, catalysts such as acids and bases, and additives such as cationic initiators, anionic initiators, and radical initiators may be added according to the reactivity of the reactive sites. For example, when an acrylate having two or more vinyl groups is used as the raw material of layer B, a coating liquid to which a radical initiator that generates radicals by ultraviolet light is added is prepared, and the coating liquid is applied to resin layer A, and then ultraviolet light is irradiated to promote the crosslinking reaction. The radical initiator is not particularly limited, but a hydroxyalkylphenone type initiator or an aminoacetophenone type initiator that generates radicals by ultraviolet light can be used. By crosslinking Layer B, it becomes easy to increase the heat resistance of the film for film capacitors of the present invention. EXAMPLES
[0048] The film for a film capacitor of the present invention will be specifically described below using examples. However, the following Examples 1, 2, 7, 10 to 12, and 14 are considered as reference examples. The methods for measuring the characteristic values and the methods for evaluating the effects are as follows.
[0049] (1) Film thickness T(F) The thickness of ten arbitrary points on the film was measured in an atmosphere of 23°C and 65% RH using a contact-type electronic micrometer (K-312A type) manufactured by Anritsu Corp. The arithmetic mean value of the thicknesses at the ten points was taken as the film thickness T(F).
[0050] (2) Thickness T(A) of resin layer A, thickness T(B) of layer B Using a microtome method, a 5 mm-wide ultrathin section having a cross section in the width direction-thickness direction of the film was prepared, and the cross section was platinum-coated to prepare an observation sample. Next, using a Hitachi field emission scanning electron microscope (S-4800), the cross section of the film was observed at an accelerating voltage of 1.0 kV, and the thickness of resin layer A and the thickness of layer B were measured from any point in the observation image. The thicker layer of the two layers was resin layer A, and the thinner layer was layer B, and the observation magnification was 10,000 times. Furthermore, the same measurement was performed a total of 20 times, and the average values were used as the thickness T(A) of resin layer A and the thickness T(B) of layer B.
[0051] (3) Melting point and glass transition temperature of resin layer A 5 mg of the resin layer A determined by the procedure described in (2) was weighed out and heated and cooled in a nitrogen atmosphere using a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments) according to the following program. <Program> Step 1: Heat from 25°C to 330°C at 10°C / min, then hold at 330°C for 5 minutes. Step 2: Cool from 330°C to 25°C at -10°C / min, then hold at 25°C for 5 minutes. Step 3: Heat from 25°C to 330°C at 10°C / min, then hold at 330°C for 5 min. During the heating process in step 3, when the DSC chart was viewed from 330°C toward the lower temperature side, the maximum temperature at which the slope of the DSC chart changed from the baseline slope was defined as T_1, and the minimum temperature at which the slope of the DSC chart returned to the baseline slope below T_1 was defined as T_2. The value Tg obtained by the following calculation formula was defined as the glass transition temperature of resin layer A. <Calculation formula> Tg=(T_1+T_2) / 2.
[0052] In addition, the peak temperature of the endothermic curve obtained in step 3 was taken as the melting point of the resin layer A, and when multiple peak temperatures were observed, the highest temperature was taken as the melting point of the resin layer A. However, if no peak was observed in the endothermic curve obtained in step 3, and if the slope of the DSC chart did not change from the slope of the baseline in the region of 25°C or higher when the DSC chart was viewed from 330°C to the low temperature side in the heating process of step 3, the melting point and glass transition temperature of the resin layer A were both taken as 330°C or higher. If no peak was observed in the endothermic curve obtained in step 3, but the glass transition temperature was less than 330°C, there was no melting point. If the slope of the DSC chart did not change from the slope of the baseline in the region of 25°C or higher when the DSC chart was viewed from 330°C to the low temperature side in the heating process of step 3, there was no glass transition temperature. In Tables 1 to 3, the corresponding cases are indicated as "-".
[0053] (4) The atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N, and oxygen atoms O contained in resin layer A and layer B, and the contents of oxygen atoms O and silicon atoms Si in layer B The surface of the film on the resin layer A side was analyzed by Rutherford backscattering / hydrogen forward scattering simultaneous measurement method (Pelletron 3SDH manufactured by National Electrostatics Corporation) to obtain the atomic yields Y(H), Y(C), Y(S), Y(Si), Y(N) and Y(O) of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N and oxygen atoms O of resin layer A. From the obtained values, the values obtained based on the following formula were regarded as the atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N and oxygen atoms O contained in resin layer A. <Calculation formula> Y(All)=Y(C)+Y(S)+Y(Si)+Y(N)+Y(O)+Y(H). Atomic fraction of hydrogen atoms H = Y(H) / Y(All) Atomic fraction of carbon atom C = Y(C) / Y(All) Atomic fraction of sulfur atom S = Y(S) / Y(All) Atomic fraction of silicon atom Si = Y(Si) / Y(All) Atomic fraction of nitrogen atom N = Y(N) / Y(All) The atomic fraction of oxygen atoms, O, is Y(O) / Y(All).
[0054] Layer B was also analyzed in the same manner, except that the surface analyzed by the Rutherford backscattering / hydrogen forward scattering simultaneous measurement method was the surface on the layer B side, and each value was calculated to determine the atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N, and oxygen atoms O contained in layer B. The contents of oxygen atoms O and silicon atoms Si in layer B were also calculated based on the following formula. Note that the atomic fractions Y(C), Y(S), Y(Si), Y(N), Y(O), and Y(H) in the formula are all for layer B. <Calculation formula> Oxygen atom content (mass%) = 100 x 16.0 x Y(O) / (12.0 x Y(C) + 32.1 x Y(S) + 28.1 x Y(Si) + 14.0 x Y(N) + 16.0 x Y(O) + 1.01 x Y(H)) Silicon atom Si content (mass%) = 100 x 28.1 x Y(Si) / (12.0 x Y(C) + 32.1 x Y(S) + 28.1 x Y(Si) + 14.0 x Y(N) + 16.0 x Y(O) + 1.01 x Y(H)) The measurement conditions are as follows. Incident ions: 4 He ++ Incident energy: 2300keV Incident angle: 75deg Scattering angle: 160deg Recoil angle: 30deg Specimen current: 4nA Beam diameter: 2mmφ In-plane rotation: None Irradiation dose: 0.5μC x 20 points (5) XA, XB Using the values obtained by the method described in (4), XB was calculated according to the following formula (A) and XA was calculated according to the following formula (B). Formula (a) XB = (atomic fraction of carbon atoms C in layer B + atomic fraction of nitrogen atoms N in layer B + atomic fraction of sulfur atoms S in layer B + atomic fraction of silicon atoms Si in layer B) / (atomic fraction of hydrogen atoms H in layer B + atomic fraction of oxygen atoms O in layer B) Equation (b) XA=(atomic fraction of carbon atoms C in resin layer A+atomic fraction of nitrogen atoms N in resin layer A+atomic fraction of sulfur atoms S in resin layer A+atomic fraction of silicon atoms Si in resin layer A) / (atomic fraction of hydrogen atoms H in resin layer A+atomic fraction of oxygen atoms O in resin layer A).
[0055] (6) Dynamic friction coefficient (μdaa, μdab, μdbb) The dynamic friction coefficient was measured at a load of 200 g, 25°C, and 65% RH using a slip tester manufactured by Toyo Seiki Co., Ltd., in accordance with JIS K 7125 (1999). When one side of the film was the α-side and the other side was the β-side, measurements were performed in two cases: when the α-sides were overlapped and when the β-sides were overlapped. Measurements were performed three times for each case, and the average value of the obtained values was calculated to be the dynamic friction coefficient when each side was measured. When the α-side and β-side were overlapped and measured, the surface with the larger dynamic friction coefficient was the a-side, and the surface with the smaller dynamic friction coefficient was the b-side, the dynamic friction coefficient between the a-sides was μdaa, and the dynamic friction coefficient between the b-sides was μdbb. Furthermore, measurements were performed three times when the a-side and the b-side were overlapped, and the average value of the obtained values was calculated to be μdab. In each case, when the friction force detected by the load cell during measurement exceeded 5.9 N, the measurement was interrupted and the measured value of the dynamic friction coefficient was recorded as >3.0. When the dynamic friction coefficients measured on the same surfaces were equal or >3.0, the surface with the higher arithmetic mean roughness Sa, measured by the method described below, was recorded as surface b.
[0056] (7) Arithmetic mean roughness Sa, areal load ratio Smr1, protruding peak height Spk, maximum valley depth Sv Each parameter was measured and calculated in accordance with ISO25178-2:2012 and ISO25178-3:2012. However, the measurements were performed using a scanning white light interference microscope "VS1540" (manufactured by Hitachi High-Tech Science Corporation; measurement conditions and device configuration are described below), and the captured image was complemented (fully complemented) using the attached analysis software, surface correction was performed using a polynomial fourth-order approximation, and then the image was processed with a median filter (3 x 3 pixels) and measured. The S-filter nesting index was set to 0.455. The measurements were performed on both sides of a film cut into a 5 cm x 5 cm square, with the intersection of the diagonals as the first measurement point (start point), and the positions 1 cm away from the start point toward each of the four corners as the second to fifth measurement points, for a total of five measurement positions, and measurements were performed at each measurement position, and Sa, Smr1, Spk, and Sv were obtained at each measurement position according to the above procedure, and the average values were adopted as Sa, Smr1, Spk, and Sv of the film. In particular, the value of Spk on side a was Spk-a, and the values of Spk and Smr1 on side b were Spk-b and Smr1-b, respectively. Spk-b / Spk-a was calculated from the obtained values of Spk-a and Spk-b. Sv / T(F) was calculated from the obtained values of Sv on each side and the above-mentioned value of T(F). <Measurement conditions and equipment configuration> Objective lens: 10x Optical tube: 1x Zoom lens: 1x Wavelength filter: 530nm white Measurement mode: Wave Measurement software: VS-Measure 10.0.4.0 Analysis software: VS-Viewer 10.0.3.0 Measurement area: 561.1μm×561.5μm Number of pixels: 1,024 x 1,024.
[0057] (8) SH defect rate, self-healing ability 25W·min / m on the surface of layer B 2 The film without layer B was subjected to corona discharge treatment in the atmosphere at a treatment intensity of 25 W·min / m on side b. 2The corona discharge treatment was then performed in the atmosphere at a treatment intensity of 1.0×10. The corona discharge treatment surface was then subjected to a bell jar type vacuum deposition apparatus at a pressure of 1.0×10. -3 Commercially available aluminum was evaporated at 2.6 Pa and a filament voltage of 2.6 kV to form a 50 nm evaporated film, and a metal layer laminate film was obtained. The obtained metal layer laminate film was cut into a rectangular shape with the long sides in the longitudinal direction and a size of 12 cm x 7.5 cm to prepare a test piece.
[0058] A 10 cm square, 1 mm thick "Teflon" (registered trademark) sheet was placed on a 1 m x 2 m copper plate. The test piece was placed on the "Teflon" (registered trademark) sheet so that the short side of the test piece was parallel to one side of the "Teflon" (registered trademark) sheet and a 1 cm area from one short side of the test piece was placed on the "Teflon" (registered trademark) sheet. The part of the test piece that was placed on the "Teflon" (registered trademark) sheet was removed by 2 cm. 2 A 5 cm square plate-shaped conductive rubber electrode was placed on the "Teflon" (registered trademark) sheet so that it was sandwiched between the test piece and the "Teflon" (registered trademark) sheet. In addition, a cylindrical electrode with a diameter of 3 cm was placed on the rubber electrode so that its center of gravity was located above the area where the rubber electrode, the test piece, and the "Teflon" (registered trademark) sheet overlapped. A so-called step-up test was performed in which a DC power source was connected to the cylindrical electrode and the copper plate via electric wires, and an initial voltage of 100 VDC was applied, and after 15 seconds at that voltage, the applied voltage was gradually increased in steps of 100 VDC / 30 seconds to the initial voltage of +800 VDC, and multiple insulation breakdown marks were generated on the metal layer laminated film.
[0059] The marks of dielectric breakdown that occurred were visually observed, and marks where two or more overlapping marks of dielectric breakdown were considered as one SH defective area, and marks where there were no overlapping marks as one normal area. The number of each was counted, and the SH defect rate was calculated using the following formula. The same measurement was performed twice, and the average value was used as the SH defect rate of the film. If no dielectric breakdown occurred, the initial voltage was set to 900VDC and the same measurement was performed. If no dielectric breakdown occurred even with an initial voltage of 10,000VDC, the SH defect rate was calculated as 0%. <Calculation formula> SH defect rate (%) = 100 x (number of SH defective parts) / (number of normal parts + number of SH defective parts) Based on the SH defect rate of the film, the self-healing property was evaluated as follows. S: The SH defect rate is 16% or less. A: The SH defect rate is greater than 16% and less than or equal to 22%. B: The SH defect rate is greater than 22% and less than or equal to 30%. C: SH defect rate is greater than 30%.
[0060] (9) Evaluation of processability 25W·min / m on the surface of layer B 2 The film without layer B was subjected to corona discharge treatment in the atmosphere at a treatment intensity of 25 W·min / m on side b. 2 The corona discharge treatment was then performed in the atmosphere at a treatment intensity of 1.0×10. The corona discharge treatment surface was then subjected to a bell jar type vacuum deposition apparatus at a pressure of 1.0×10. -3 Commercially available aluminum was vapor-deposited at 1000 Pa and a filament voltage of 2.6 kV to form a vapor-deposited film of 50 nm, to obtain a metal layer laminated film. The obtained metal layer laminated film was cut into a rectangular shape of 12 cm x 7.5 cm with the long side in the longitudinal direction to obtain a test piece. Using a slip tester manufactured by Toyo Seiki Co., Ltd., the dynamic friction coefficient between the metal vapor-deposited surface and the surface on which metal was not vapor-deposited of the obtained metal layer laminated film was measured three times in accordance with JIS K 7125 (1999) at a load of 200 g, 25 ° C, and 65% RH, and the average value of the obtained values was taken as the dynamic friction coefficient μM of the metal laminated film. Note that when the friction force detected by the load cell during the measurement exceeded 5.9 N, the measurement was interrupted, and the measured value of μM in that case was taken as > 3.0. Based on the obtained μM, the processability of the film was judged according to the following criteria. S:μM is less than 0.60. A: μM is greater than 0.60 and less than 0.90. B: μM is greater than 0.90 and less than or equal to 1.5. C: μM greater than 1.5.
[0061] (10) Dielectric tangent The dielectric loss tangent was measured according to JIS C2138-2007. First, the film was cut into a 6 cm x 6 cm square and a 25 W·min / m 2 The film without layer B was subjected to corona discharge treatment in the atmosphere at a treatment intensity of 25 W·min / m on side b. 2 The corona discharge treatment was then performed in the atmosphere at a treatment intensity of 1.0×10. The corona discharge treatment surface was then subjected to a bell jar type vacuum deposition apparatus at a pressure of 1.0×10. -3 Commercially available aluminum was evaporated at a pressure of 1.0 × 10 Pa and a filament voltage of 2.6 kV to form a circular thin-film electrode with a diameter of 5.0 cm and a thickness of 50 nm. The surface of the film that had not been corona discharge-treated was then evaporated in a bell-jar vacuum deposition apparatus at a pressure of 1.0 × 10 Pa and a filament voltage of 2.6 kV, so that the center of the electrode formed on the corona discharge-treated surface was aligned with the center of the electrode. -3 Commercially available aluminum was evaporated at 2.6 Pa and a filament voltage of 2.6 kV to form a circular thin-film electrode with a diameter of 5.6 cm and a thickness of 50 nm to obtain a test piece. The dielectric tangent of the obtained test piece was measured by the contact method at 23°C, a relative humidity of 50%, a frequency of 10 kHz, n=5, using an E4980A precision LCR meter (manufactured by Keysight Technologies), and the average of the obtained values was taken as the dielectric tangent of the film.
[0062] (11) Evaluation of film breakdown voltage at 150℃ After heating the film for 1 minute in an oven maintained at 150°C, measurements were made in that atmosphere in accordance with JIS C2330(2001)7.4.11.2 Method B (Plate Electrode Method). However, for the lower electrode, a conductive rubber E-100 manufactured by Togawa Rubber Co., Ltd. of the same dimensions was placed on the metal plate described in JIS C2330(2001)7.4.11.2 Method B. <65> " was used. The dielectric breakdown voltage test (above measurement) was performed 30 times, and the obtained value was divided by the film thickness (measured in (1) above) and converted to (V / μm) to obtain a total of 30 measured values (calculated values). Of these, the 5 largest values and the 5 smallest values were excluded, and the average of these 20 values was calculated, which was taken as the film dielectric breakdown voltage at 150°C. From the obtained film dielectric breakdown voltage at 150°C, the film dielectric breakdown voltage at 150°C was evaluated as follows. S: The film had a dielectric breakdown voltage of 270 V / μm or more at 150° C. A: The film dielectric breakdown voltage at 150°C was 240 V / μm or more and less than 270 V / μm. B: The film had a dielectric breakdown voltage of 210 V / μm or more and less than 240 V / μm at 150° C. C: The film had a dielectric breakdown voltage of 100 V / μm or more and less than 210 V / μm at 150° C. D: The film dielectric breakdown voltage at 150° C. was less than 100 V / μm or the film shrinkage was so great that it could not be evaluated.
[0063] (12) Evaluation of film capacitor characteristics (reliability at 150℃) 25 W·min / m on the surface of layer B of the film 2 The film without layer B was subjected to corona discharge treatment in the atmosphere at a treatment intensity of 25 W·min / m on side b. 2 A corona discharge treatment was performed in the atmosphere at a treatment intensity of 10 ... After increasing the voltage until the capacitance decreased to 12% or less of the initial value, the capacitor element was disassembled to check the state of destruction, and the film capacitor characteristics were evaluated as follows. S: There was no change in the shape of the film capacitor element, and no penetration damage was observed. A: There was no change in the shape of the film capacitor element, but penetration damage was observed within 5 layers of the film. B: There was no change in the shape of the film capacitor element, and penetration damage penetrating through layers 6 and 7 of the film was observed. C: Changes in the shape of the film capacitor element were observed, or penetration damage was observed in 8 to 14 layers of the film. D: The shape of the film capacitor element was significantly changed and destroyed, or the film was poorly processable, and a film capacitor element could not be produced. -: Film capacitor characteristics were not evaluated. S can be used without any problems, A can be used depending on the conditions, B is inferior in practical performance but usable, C is inferior in practical performance depending on the conditions but usable. D is practically difficult to use as a capacitor film.
[0064] [Resin, film, coating liquid] Polyphenylene sulfide resin granules 1 (PPS granules 1): In a 1-liter autoclave equipped with a process stirrer, 1.00 mol of 47% by mass sodium hydrosulfide, 1.02 mol of 96% by mass sodium hydroxide, 1.56 mol of N-methyl-2-pyrrolidone (NMP), 0.46 mol of sodium acetate, and 140 g of ion-exchanged water were charged, and while stirring at 250 rpm and passing nitrogen at normal pressure, the mixture was gradually heated to 225°C over about 3 hours, and 212 g of water and 4 g of NMP were distilled, and the reaction vessel was cooled to 160°C. Next, 1.00 mol of p-dichlorobenzene (p-DCB) and 1.32 mol of NMP were added, and the reaction vessel was sealed under nitrogen gas. Then, while stirring at 240 rpm, the temperature was raised from 200°C to 235°C at a rate of 0.6°C / min, and after reaching 235°C, the reaction was continued at 235°C for 95 minutes. Then, the temperature was raised to 270°C at a rate of 0.8°C / min and held for 100 minutes. At this time, after reaching 270°C, 1 mole of water was injected into the system over 15 minutes. After holding at 270°C for 100 minutes, it was cooled to 200°C at a rate of 1.0°C / min, and then cooled to near room temperature by applying room temperature cooling water to the autoclave. Next, the contents were taken out, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were filtered off with a sieve (80 mesh). Furthermore, 0.5 liters of NMP was added to the obtained solid, stirred at 85°C for 30 minutes, and the solids were filtered off. Then, the obtained solids were washed three times with 0.9 liters of warm water and filtered off. The particles (solids) thus obtained were washed twice with 1 liter of warm water and filtered off to obtain polymer particles. This was dried with hot air at 80° C. and then dried under reduced pressure at 120° C. to obtain polyphenylene sulfide (PPS) resin granules (PPS granules 1) having a melting point of 280° C. and a weight average molecular weight of 70,000.
[0065] PPS raw material for film 1 (PPS1): PPS granules 1 were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 320°C, melt-extruded at a residence time of 90 seconds and a screw rotation speed of 150 rpm, discharged in the form of strands, and cooled with water at a temperature of 25°C. They were then immediately cut into chips to produce PPS raw material 1 for film (PPS1).
[0066] PPS raw material for film (PPS2): 100 parts by mass of PPS granules 1, 0.05 parts by mass of calcium carbonate particles 1 ("NITOREX" #30PS, manufactured by Nitto Funka Kogyo Co., Ltd.) with an average particle size of 0.7 μm, and 0.2 parts by mass of calcium stearate were mixed and pelletized to prepare a resin pellet mainly composed of PPS. The resin pellets obtained were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 320 ° C, melt extruded at a residence time of 90 seconds and a screw rotation speed of 150 rpm, discharged in the form of a strand, and cooled with water at a temperature of 25 ° C. Then, they were immediately cut to prepare chips, which were used as PPS raw material 2 for film (PPS2).
[0067] PPS film 1: As a raw material, PPS1 was vacuum dried at 180°C for 3 hours. Then, it was fed into an extruder, melted at a temperature of 320°C under a nitrogen atmosphere, and introduced into a T-die die. Then, it was extruded into a sheet form from the T-die die to form a molten single-layer sheet, which was discharged onto a cast drum with a rotation speed of 4.0 m / min and a surface temperature of 25°C, and cast by cooling and solidifying it by contacting with an electrostatic application method to obtain an unstretched film. The obtained unstretched film was stretched at a stretching temperature of 103°C in the longitudinal direction of the film at a ratio of 3.1 times using a longitudinal stretching machine consisting of a plurality of heated rolls, utilizing the difference in peripheral speed of the rolls. Then, both ends of the obtained uniaxially stretched film in the width direction were supported by clips and introduced into a tenter, where it was stretched at a stretching temperature of 100°C in the width direction at a ratio of 3.3 times. Subsequently, it was heat-treated at 280°C, followed by 2% relaxation treatment and cooling to room temperature. Then, the film surface (the side that comes into contact with the casting drum) is subjected to a current of 25 W·min / m 2 After that, the film edges were removed to obtain a biaxially oriented PPS film having a thickness of 4.5 μm.
[0068] PPS film 2: A biaxially stretched PPS film having a thickness of 4.6 μm was obtained in the same manner as in the production of PPS film 1, except that PPS2 was used instead of PPS1 as the raw material.
[0069] Coating fluid 1: A coating liquid obtained by mixing 70 g of acrylate (I) (product name "Viscoat" #300, a condensate of pentaerythritol and acrylic acid, containing 45% by mass of pentaerythritol tetraacrylate and 35% by mass of pentaerythritol triacrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 50 g of cellulose acetate (i) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., acetylation rate 54%), 880 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone).
[0070] Coating fluid 2: A coating liquid obtained by mixing 70 g of acrylate (II) (trade name "EBECRYL" (registered trademark) 150, manufactured by Daicel-Allnex Corporation, ethylene oxide modified bisphenol A diacrylate), 30 g of cellulose acetate (i), 900 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone).
[0071] Coating fluid 3: A coating liquid obtained by mixing 80 g of acrylate (I), 11 g of epoxy resin (product name "EPICLON" 850, active group equivalent 189 eq / g, manufactured by DIC Corporation), 9.0 g of active ester (product name "HPC-8000-65T", active group equivalent 223 eq / g, manufactured by DIC Corporation), 900 g of 2-butanone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone), and 10 mg of 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0072] Coating fluid 4: A coating liquid obtained by mixing 99.5 g of acrylate (II), 500 mg of acrylic resin (product name "MP-1451", non-crosslinked acrylic particles, manufactured by Soken Chemical & Engineering Co., Ltd., average particle size 150 nm), 900 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone).
[0073] Coating fluid 5: A coating liquid obtained by mixing 54 g of epoxy resin (product name "EPICLON" (registered trademark) 850, active group equivalent 189 eq / g, manufactured by DIC Corporation), 45.5 g of active ester (product name "HPC-8000-65T", active group equivalent 223 eq / g, manufactured by DIC Corporation), 500 mg of acrylic resin (product name "MP-1451", non-crosslinked acrylic particles, manufactured by Soken Chemical & Engineering Co., Ltd., average particle size 150 nm), 900 g of 2-butanone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 10 mg of 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0074] Coating fluid 6: A coating liquid obtained by mixing 65 g of acrylate (I), 35 g of terpene phenol resin (product name "TH130", manufactured by Yasuhara Chemical Co., Ltd.), 900 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone).
[0075] Coating fluid 7: A coating liquid was prepared by mixing 500 mg of acrylic resin (product name "MP-1451", non-crosslinked acrylic particles, manufactured by Soken Chemical & Engineering Co., Ltd., average particle size 150 nm), 99.5 g of cellulose acetate (i), and 900 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0076] Coating fluid 8: A coating liquid obtained by mixing 99.9 g of nitrile butadiene rubber (product name "Nipol" (registered trademark) DN003, manufactured by Zeon Corporation, Mooney viscosity 77.5), 100 mg of calcium carbonate particles 2 (product name "CALUCEO" (registered trademark) P015S0, particle size 150 nm), and 900 g of 2-butanone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.).
[0077] Coating fluid 9: A coating liquid obtained by mixing 54 g of epoxy resin (product name "EPICLON" (registered trademark) 850, active group equivalent 189 eq / g, manufactured by DIC Corporation), 45.5 g of active ester (product name "HPC-8000-65T", active group equivalent 223 eq / g, manufactured by DIC Corporation), silica particles (y) (average particle size 0.1 μm, "Seahoster" (registered trademark) KE-P10, manufactured by Nippon Shokubai Co., Ltd.), 900 g of 2-butanone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 10 mg of 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0078] Coating fluid 10: A coating liquid obtained by mixing 100 g of acrylate (I), 900 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 200 mg of Omnirad184 (manufactured by IGM Resins BV, 1-hydroxycyclohexyl phenyl ketone).
[0079] Coating Fluid 11: A coating liquid obtained by mixing 99.5 g of polyetherimide (product name "ULTEM" (registered trademark) Resin 1010, manufactured by SABIC, glass transition temperature 217°C), 500 mg of calcium carbonate particles 2, and 900 g of N-methylpyrrolidone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.).
[0080] Example 1 15 g of polyetherimide resin (trade name "ULTEM" (registered trademark) Resin 1010, manufactured by SABIC, glass transition temperature 217 ° C.) was dissolved in 85 g of N-methyl-2-pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare an NMP solution of polyetherimide. This was applied to a commercially available polyimide film (thickness 140 μm) using a #20 metabar, and dried in an oven at 150 ° C. for 15 minutes to form a polyetherimide resin layer (resin layer A) on the polyimide film. Next, 2.1 g of terpene phenol resin (trade name "TH130", manufactured by Yasuhara Chemical Co., Ltd.), 25 mg of silica particles (x) (average particle size 0.7 μm, "Sunseal" (registered trademark) SS-07, manufactured by Tokuyama Corporation), and 12 g of 2-butanone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed to prepare a coating liquid in which the terpene phenol resin was dissolved. This was applied to the polyetherimide resin layer on the polyimide film using #4 Metabar and dried in an oven at 100°C for 1 minute to form a coating layer (layer B) on the polyetherimide resin layer. The laminate of the polyetherimide resin layer and the coating layer was peeled off from the polyimide film to obtain a film for film capacitors. The evaluation results are shown in Table 1.
[0081] Example 2 A film for a film capacitor was obtained in the same manner as in Example 1, except that the mixed amounts of the terpene phenol resin, the silica particles (x), and 2-butanone were 0.70 g, 8 mg, and 14.2 g, respectively. The evaluation results are shown in Table 1.
[0082] Example 3 Coating liquid 1 was uniformly applied to the corona-treated surface of PPS film 1 (resin layer A) using a bar coater so that the thickness of layer B after curing would be 0.10 μm, and then it was dried in a drying oven at 90° C. for 1 minute. It was then introduced into a UV irradiation device and exposed to an illumination intensity of 50 mW / cm 2 , irradiation amount 0.1J / cm 2 The coating was cured under conditions of an oxygen concentration of 100 ppm to form Layer B, and then the laminate of Layer A and Layer B was wound up to obtain a film for film capacitors. The evaluation results are shown in Table 1.
[0083] Example 4 A film for film capacitors was obtained in the same manner as in Example 3, except that Coating Liquid 2 was used instead of Coating Liquid 1. The evaluation results are shown in Table 1.
[0084] Example 5 A film for a film capacitor was obtained in the same manner as in Example 3, except that Coating Liquid 3 was used instead of Coating Liquid 1, and the drying temperature in the drying oven was set to 120° C. The evaluation results are shown in Table 1.
[0085] Example 6 A film for a film capacitor was obtained in the same manner as in Example 3, except that Coating Liquid 4 was used instead of Coating Liquid 1. The evaluation results are shown in Table 1.
[0086] Example 7 A film for a film capacitor was obtained in the same manner as in Example 3, except that Coating Liquid 5 was used instead of Coating Liquid 1. The evaluation results are shown in Table 1.
[0087] Example 8 150g of polyetherimide resin was dissolved in 850g of N-methyl-2-pyrrolidone to prepare a polyetherimide NMP solution. This was uniformly coated on a commercially available polyimide film (thickness 140μm) using a bar coater so that the thickness of the polyetherimide layer after drying was 3μm, and introduced into a drying oven at 150°C and dried for 5 minutes to form a polyetherimide resin layer (resin layer A) on the polyimide film. Coating liquid 6 was uniformly coated on the surface of the resin layer A side of the obtained laminate using a bar coater so that the thickness of layer B after curing was 0.1μm, and then dried in a drying oven at 90°C for 1 minute. Subsequently, it was introduced into a UV irradiation device and dried at an illuminance of 50mW / cm 2 , irradiation amount 0.1J / cm 2 The coating was cured under conditions of an oxygen concentration of 100 ppm to form Layer B. Next, the laminate of Resin Layer A and Layer B was peeled off from the polyimide film and rolled up to obtain a film for film capacitors. The evaluation results are shown in Table 2.
[0088] Example 9 As in Example 8, a polyetherimide resin layer (resin layer A) was formed on a commercially available polyimide film, and coating liquid 7 was applied onto resin layer A using a bar coater so that the thickness of layer B after drying would be 0.10 μm, and layer B was formed by drying in a drying oven at 90° C. for 1 minute. Thereafter, the laminate of resin layer A and layer B was peeled off from the polyimide film and wound up to obtain a film for film capacitors. The evaluation results are shown in Table 2.
[0089] Example 10 A film for a film capacitor was obtained in the same manner as in Example 3, except that Coating Liquid 9 was used instead of Coating Liquid 1. The evaluation results are shown in Table 2.
[0090] Example 11 A film for film capacitors was obtained in the same manner as in Example 3, except that PPS film 2 was used instead of PPS film 1 and coating liquid 10 was used instead of coating liquid 1. The evaluation results are shown in Table 2.
[0091] Example 12 A film for film capacitors was obtained in the same manner as in Example 3, except that Coating Liquid 11 was used instead of Coating Liquid 1, the temperature of the drying oven was changed from 90° C. to 150° C., and the drying time was changed from 1 minute to 5 minutes. The evaluation results are shown in Table 2.
[0092] Example 13 100 g of cellulose acetate (i) was dissolved in 900 g of methyl ethyl ketone to prepare a methyl ethyl ketone solution of cellulose acetate. This was applied to a commercially available polyimide film (thickness 140 μm) using a bar coater so that the thickness of the cellulose acetate layer after drying was 3.2 μm, and the film was introduced into a drying oven at 100 ° C. and dried for 2 minutes to form a cellulose acetate resin layer (resin layer A) on the polyimide film. Next, the coating liquid 7 was applied to the surface of the resin layer A side of the obtained laminate using a bar coater so that the thickness of layer B after curing was 0.10 μm, and the film was introduced into a drying oven at 100 ° C. and dried for 1 minute to form layer B on resin layer A. The laminate of resin layer A and layer B was peeled off from the polyimide film and wound up to obtain a film for a film capacitor. The evaluation results are shown in Table 2.
[0093] Example 14 150g of polyetherimide resin was dissolved in 850g of N-methyl-2-pyrrolidone to prepare a polyetherimide NMP solution. This was uniformly coated on a commercially available polyimide film (thickness 140μm) using a bar coater so that the polyetherimide layer after drying would be 3μm thick, and then introduced into a drying furnace at 150°C and dried for 5 minutes to form a polyetherimide resin layer (resin layer A) on the polyimide film. A silicone composition (Shin-Etsu Chemical Co., Ltd., silicone X-40-2655A) was deposited on the surface of the resin layer A side of the obtained laminate by vacuum deposition to a thickness of 0.1μm. Subsequently, a glow discharge treatment was performed on the coating layer surface by generating a glow discharge using a 250kHz, 5kW pulse DC power source while supplying a small amount of O2 gas (treatment power density E=27.8W·min / m 2 ) to form Layer B. The resulting laminate was wound up to obtain a film for film capacitors. The evaluation results are shown in Table 2.
[0094] Comparative Example 1 A film for a film capacitor consisting only of layer A was obtained in the same manner as in Example 1, except for omitting the step of forming layer B after forming resin layer A. The evaluation results are shown in Table 3.
[0095] Comparative Example 2 Coating solution 8 was applied to the corona-treated surface of PPS film 1 (resin layer A) using a bar coater so that the thickness of layer B after curing would be 0.50 μm, and the layer was dried in an oven at 90° C. for 1 minute to form layer B, thereby obtaining a film for film capacitors. The evaluation results are shown in Table 3.
[0096] Comparative Example 3 The PPS film 1 was evaluated as a film for a film capacitor. The evaluation results are shown in Table 3.
[0097] Comparative Example 4 The PPS film 2 was evaluated as a film for a film capacitor. The evaluation results are shown in Table 3.
[0098] Comparative Example 5 A polyetherimide resin (manufactured by SABIC Innovative Plastics, product name: ULTEM1010-1000-NB (hereinafter abbreviated as "1010-1000")) was prepared as the molding material for resin layer A, and this molding material was left to dry for 12 hours in a dehumidified hot air dryer (manufactured by Matsui Manufacturing Co., Ltd., product name: Multijet MJ3) heated to 150°C. After confirming that the moisture content of this molding material was 300 ppm or less, the molding material was set in a φ40 mm single-screw extruder equipped with a 900 mm wide T-die and melt-kneaded, and this melt-kneaded molding material was continuously extruded from the T-die of the single-screw extruder to extrude a polyetherimide resin film into a strip shape, thereby producing a polyetherimide resin layer 1000 m long and 65 cm wide. The cylinder temperature of the single-screw extruder was adjusted to 360 to 380°C, the temperature of the T-die to 385°C, and the temperature of the connecting pipe connecting the single-screw extruder and the T-die to 380°C. When the molding material was fed into the single-screw extruder, 18 L / min of nitrogen gas, which is an inert gas, was supplied. The formed polyetherimide resin layer was sequentially wound around a pair of pressure rolls equipped with silicone rubber having an arithmetic mean roughness (Ra) of 0.44 to 0.47 μm, a metal roll which is a cooling roll at 205°C and has a convex pattern having an arithmetic mean roughness (Ra) of 1.28 μm on its circumferential surface, and a 6-inch take-up tube located downstream of these, and was cooled by being sandwiched between each pressure roll and the metal roll. By sandwiching the polyetherimide resin layer between the pressure roll and the metal roll, a plurality of fine uneven portions were formed on the front and back surfaces of the polyetherimide resin layer. The resulting polyetherimide resin layer with fine irregularities on its surface was used as resin layer A. Di-paraxylylene was vaporized under conditions of 180°C and 10 Pa, pyrolyzed under conditions of 680°C and 10 Pa, and the diradical paraxylylene monomer obtained by pyrolysis was polymerized on the metal roll side of resin layer A under conditions of 35°C and 10 Pa to form layer B made of polyparaxylylene resin. The resulting laminate was wound up to obtain a film for film capacitors. The evaluation results are shown in Table 3.
[0099] Comparative Example 6 A linear polypropylene resin polymerized with a Ziegler-Natta catalyst, with a mesopentad fraction of 0.98, a melting point of 167°C, and a melt flow rate (MFR) of 2.6g / 10min, was fed to a single-screw melt extruder, melt extruded at 240°C, and after removing foreign matter with a sintered filter with a cutoff of 80μm, the molten polymer was discharged from a T-die, and the molten sheet was adhered to a casting drum maintained at 95°C by electrostatic application and cooled and solidified to obtain an unstretched sheet. The sheet was then gradually preheated to 145°C with a group of rolls, and passed between rolls with a difference in peripheral speed while still maintained at a temperature of 145°C, and stretched 5.0 times in the longitudinal direction. The film was then introduced into a tenter and stretched 8 times in the width direction at a temperature of 165°C, then heat-treated at 130°C while providing 8% relaxation in the width direction as the first heat treatment and relaxation treatment, and further heat-treated at 140°C while holding the film in the width direction with clips as the second heat treatment. After a cooling process at 100°C, the film was introduced to the outside of the tenter, the clips at the film ends were released, and the film with a thickness of 3.0 μm was wound up to obtain a film for film capacitors. The evaluation results are shown in Table 3.
[0100] [Table 1]
[0101] [Table 2]
[0102] [Table 3]
[0103] In addition, for Example 1, Example 2, and Comparative Example 1, the films were produced in sheets, and a film of sufficient length for processing the capacitor element could not be obtained, so capacitor element processing and evaluation of the film capacitor characteristics were not performed. [Industrial Applicability]
[0104] The film for film capacitors of the present invention can be used for various applications such as packaging applications, tape applications, cable wrapping, and electrical applications including capacitors, and can be particularly used for high-voltage capacitor applications requiring high voltage resistance and reliability at high temperatures.
Claims
1. a resin layer A having a melting point of 180° C. or more and / or a glass transition temperature of 130° C. or more, and a layer B having a thickness smaller than that of the resin layer A in at least one outermost layer of the film, the layer B having an oxygen atom content of 21% by mass or more, The layer B satisfies the following condition (i), When the dynamic friction coefficient is measured between the same surfaces of two outermost layer surfaces, the surface having a larger dynamic friction coefficient is designated as surface a and the surface having a smaller dynamic friction coefficient is designated as surface b, the dynamic friction coefficient between the a surfaces is designated as μdaa, and the dynamic friction coefficient between the a surface and the b surface is designated as μdab, μdaa>μdab and μdab≦1.2 are satisfied, A film for film capacitors in which the maximum valley depth Sv of both outermost layer surfaces satisfies Sv / T(F)<0.30, where T(F) is the film thickness. Condition (i): The value XB calculated from the atomic fractions of hydrogen atoms H, carbon atoms C, sulfur atoms S, silicon atoms Si, nitrogen atoms N, and oxygen atoms O contained in the layer B based on the following formula (i) is 0.70 or less. Formula (A) XB=(atomic fraction of carbon atoms C in the layer B+atomic fraction of nitrogen atoms N in the layer B+atomic fraction of sulfur atoms S in the layer B+atomic fraction of silicon atoms Si in the layer B) / (atomic fraction of hydrogen atoms H in the layer B+atomic fraction of oxygen atoms O in the layer B)
2. 2. The film for a film capacitor according to claim 1, having a dielectric loss tangent of 2.0% or less.
3. 3. The film for a film capacitor according to claim 1, wherein the content of silicon atoms Si in the layer B is 27 mass% or less.
4. 4. The film for film capacitors according to claim 1, wherein at least one outermost layer surface satisfies a load area ratio Smr1 separating the protruding peak portion and the core portion of ≧12%.
5. 5. The film for a film capacitor according to claim 1, wherein a ratio of the protruding peak height Spk-a of said surface a to the protruding peak height Spk-b of said surface b satisfies Spk-b / Spk-a≧2.0, and a load area ratio Smr1-b separating the protruding peaks and a core portion of said surface b satisfies Smr1-b≧12%.
6. The film for a film capacitor according to any one of claims 1 to 5, wherein the layer B contains two or more components that are incompatible with each other.
7. The resin layer A contains at least one resin selected from the group consisting of polyphenylene sulfide resin, polyetherimide resin, polyphenylsulfone resin, and polyethersulfone resin in an amount of 50% by mass to 100% by mass. The film for film capacitors according to any one of claims 1 to 6.
8. The film for film capacitors according to any one of claims 1 to 7, wherein the layer B contains 50% by mass or more and 100% by mass or less of at least one resin selected from the group consisting of an acrylic resin, an epoxy resin, a cellulose derivative, and a polyester resin.
9. A metal layer laminated film for film capacitors, comprising the film for film capacitors according to any one of claims 1 to 8, and a metal layer on at least one outermost layer surface.
10. The metal layer laminate film for a film capacitor according to claim 9, comprising the resin layer A, the layer B, and the metal layer in this order.
11. 11. The metal layer laminate film for a film capacitor according to claim 10, wherein the resin layer A has the layer B only on one side thereof, the metal layer is on the layer B side, and when the surface having a larger dynamic friction coefficient measured between the two outermost layer surfaces is designated as surface a and the surface having a smaller dynamic friction coefficient measured between the same surfaces is designated as surface b, the surface b is on the layer B side as viewed from the resin layer A.
12. A film capacitor comprising the metal layer laminate film for a film capacitor according to any one of claims 9 to 11.
Citation Information
Patent Citations
Polyphenylene sulfide laminated film and capacitor using the same film
JP1992219236A
Polyester film for capacitor
JP2004103787A
High temperature capacitor and method of manufacturing the same
JP2007300126A
Substrate film and manufacturing method thereof
JP2018163950A
Manufacturing processes for forming metallized film capacitors and related metallized film capacitors
US20170062144A1